A New Paradigm In Economy About Maqashid Al-Sharia Theory: Reformulation Of Ibn-Asyur - Nur Rofiq; M Zidny Nafi Hasbi (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: This article examines the theory of sharia maqasid based on the thoughts of Ibn Assyria. Maqasid sharia, as one of the most important concepts in the study of Islamic law, is a universal goal that will be achieved by sharia and realized in life. There is a large framework of sharia maqasid according to Ibn Assyria, namely the principle of Qashdi, the principle of responsibility, the principle of Istikhlaf and Fitrah, and the principle of equality. The objectives of sharia that ibn Assyria has set are Kath's.Purposes of the Research: To elaborate the paradigm of sharia maqasid, especially in terms of economics as the fruit of thought from Ibn Assyria.Methods of the Research: This research uses qualitative research methods where the data is based on literature studies.Results of the Research: For Maqasih sharia is not separated from maslahah. Ibn Assyria sets out on five criteria to recognize which are categorized as maslahah and masadah among others: (1) Benefits and mudharat on a thing must exist and manifest in general nature. (2) Real and clear benefits and benefits in circumstances acceptable to common sense, so as not to contradict reason and logic. (3) All things that cannot be replaced in bringing about a maslhah and mudharat. (4) Its benefits and mudharat have things that can both be measured and chosen. (5) Its benefits and benefits are standardized on the obvious. (3) All things that cannot be replaced in bringing about a maslhah and mudharat. (4) Its benefits and mudharat have things that can both be measured and chosen. (5) Its benefits and benefits are standardized on the obvious. (3) All things that cannot be replaced in bringing about a maslhah and mudharat. (4) Its benefits and mudharat have things that can both be measured and chosen. (5) Its benefits and benefits are standardized on the obvious.